Islamic Harmony in Diversity and Cross-Cultural Relations in Indonesia - Saputra, Edriagus; Samad, Duski; Gustianda, Nana; Itrayuni, Itrayuni; Andika, Erwin Saputra; Eramahi, Eka; Kirin, Arwansyah (Jurnal Kajian dan Pengembangan Umat, 2025)
This research examines harmony in diversity and local cultural relations in Indonesia with a focus on the history of the entry of Islam, the balance of community life between religion and local culture, and efforts to build Islamic harmony in cultural diversity. The research approach used is a qualitative method with digital source-based data collection techniques. The research data was obtained through Dimensions, Google Scholar, and Publish or Perish applications to search for relevant literature, while data analysis was carried out with the help of Sciscape and VorViewers to map concept interactions and related scientific networks. The results show that the entry of Islam into Indonesia took place through trade, da'wah, and cultural assimilation that allowed Islam to adapt to local wisdom without eliminating the essence of religious teachings. The balance between Islamic teachings and local culture is reflected in various aspects of community life, including traditions, arts, and social systems that accommodate Islamic values without ignoring local cultural identity. In addition, this research found that efforts to build Islamic harmony in the diversity of local cultures in Indonesia require an inclusive approach, intercultural dialogue, and the active role of religious leaders and traditional leaders in aligning religious understanding with cultural values that have long developed in society. Thus, this research contributes to understanding how Islam and local culture can interact harmoniously without causing identity conflicts. The implications of this research are expected to serve as a basis for policy-making in building an inclusive, tolerant and civilised society, as well as a reference for further studies related to the relationship between religion and culture in the Indonesian context.